Soil aggregate stability Cropping system effects, spatial variability and contribution to potato yield in Michigan - Po, Edgar Allan C. (Michigan State University, 2007)
Soil structure stability must be maintained to facilitate gaseous and water exchange between the root and its external environment, ensuring optimum potato crop productivity in the process. Seven potato rotation systems (2-year) with varying amounts of carbon (C) inputs were evaluated over 3 years beginning in 2001, for their effects on the dynamics of water stable soil aggregation (WSA) and C sequestration at a field trial located in Central Michigan on an irrigated Alfisol. The systems consisted of four main crops (potato, snapbean, corn, wheat) and three winter cover crops (rye, hairy vetch, and red clover). Regression and correlation analyses were conducted on the relationship of WSA and digital imagery sources (i.e., in-field and archived high-resolution imageries) to potato yield in 2003 and 2004 from two commercial fields. Systems involving sweet corn contributed 2-fold higher biomass than those with wheat or snapbean, and presence of a legume in a cover crop system contributed significantly higher amounts of C inputs (1.2 Mgha-1) compared to presence of rye alone (0.7 Mgha-1). In 2004, macro-WSAs declined by 13% from 2001 levels for all systems except those with high C inputs, which maintained macroaggregates. Residue C input was a moderate predictor of total soil C (31% of variability explained), whereas macro and micro WSAs were significant predictors of total soil C, accounting for 58 and 72% of observed variability, respectively. Results from the two commercial fields' stepwise and principal component regression analyses explained an average of 63% and 54% of the yield variance. The positive contribution of soil structure stability to yield indicates the need for its management. Use of cereals as rotation crop with potato and leguminous cover crop appeared to be an effective means to improve soil structure stability. In-season use of digital imagery can potentially aid in pre-harvest yield mapping and monitoring of important soil physical attributes.